Patient Identified Barriers to Completing Advance Directives - Shotwell, Marnie (My University, 2024)
Advance Care Directives (ACD) are legal documents that identify a healthcare power of attorney and personal choices about medical interventions an individual would or would not want if unable to speak for themselves. A healthcare power of attorney identifies someone to advise medical care a patient would want or not want and a living will identify what interventions a patient may want. They aide healthcare providers with implementation of appropriate medical interventions when a patient is unable to decide at that moment. Although all legally competent people over age 18 can have one or both of these forms, the Centers for Disease Control (CDC) has reported that less than 30% of people have these documents completed (2018).
Keywords: Advance Care Directives